2021
DOI: 10.1016/j.heliyon.2021.e07812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiation hazard indices due to natural radioactivity in soil samples from Orlu, Imo State, Nigeria

Abstract: The use of a Radiation Alert Inspector device and a gamma-spectrometry system fitted with a Sodium Iodide (NaI) detector was used to determine the radioactivity concentration level of natural radionuclides 238 U, 232 Th, and 40 K in soil in several locations in Orlu, Imo State, Nigeria. 19 soil samples were collected for analysis from several locations of factories, agricultural farming-lands, gullies and water eroded areas, and soil deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 9 publications
2
23
4
Order By: Relevance
“… 54 The average concentration of 232 Th obtained in this study is lower than those obtained in other parts of the country except for Imo State. 48 - 54 However, 40 K average concentration in the present study is higher than those obtained in most part of the country except for Ondo State.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“… 54 The average concentration of 232 Th obtained in this study is lower than those obtained in other parts of the country except for Imo State. 48 - 54 However, 40 K average concentration in the present study is higher than those obtained in most part of the country except for Ondo State.…”
Section: Discussioncontrasting
confidence: 78%
“…Comparison of the level of radionuclide concentrations obtained in this study with similar studies previously carried out in Nigeria by other researchers is shown in Table 2 . The study revealed that average 238 U concentration in this study is higher than those obtained in parts of Imo, Ondo, Edo, and Benue 48 - 54 States. The value however compares with the average value obtained for the 6 geopolitical zones of Nigeria.…”
Section: Discussioncontrasting
confidence: 64%
“…Worth of note, the AEDE was calculated for both "outdoor" and "indoor" exposure [27], in order to take into account all possible exposure contexts, i.e. archaeological sites, museums, churches, in which these pigments can be found [28].…”
Section: Hpge Gem Detectormentioning
confidence: 99%
“…Background ionizing radiation was initially present in human surroundings because natural terrestrial radionuclide and extraterrestrial cosmic radiation sources had been enhanced over the years due to various human activities, especially in industrialized areas. These enhanced radiation levels in the human environment expose them to acute radiological hazards [16,17].…”
Section: Introductionmentioning
confidence: 99%